2020
DOI: 10.1038/s42003-020-0791-x
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin 5-HT4 receptor boosts functional maturation of dendritic spines via RhoA-dependent control of F-actin

Abstract: Activity-dependent remodeling of excitatory connections underpins memory formation in the brain. Serotonin receptors are known to contribute to such remodeling, yet the underlying molecular machinery remains poorly understood. Here, we employ high-resolution time-lapse FRET imaging in neuroblastoma cells and neuronal dendrites to establish that activation of serotonin receptor 5-HT 4 (5-HT 4 R) rapidly triggers spatially-restricted RhoA activity and G13-mediated phosphorylation of cofilin, thus locally boostin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 82 publications
2
30
0
Order By: Relevance
“…It has been suggested that 5‐HT 4 R activity might affect overall network excitability (Schill et al, 2020). We investigated whether the manipulation of 5‐HT 4 R signaling in astrocytes affected glutamatergic synaptic transmission.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that 5‐HT 4 R activity might affect overall network excitability (Schill et al, 2020). We investigated whether the manipulation of 5‐HT 4 R signaling in astrocytes affected glutamatergic synaptic transmission.…”
Section: Discussionmentioning
confidence: 99%
“…The 5-HT 4 R activates the heterotrimeric G 13 protein, resulting in RhoA-dependent neurite retraction and cell rounding under basal conditions and after agonist stimulation (Ponimaskin et al, 2002). Moreover, our recent study provided evidence that the 5-HT 4 R-G 13 -RhoA signaling cascade stimulates phosphorylation of the actin-binding protein cofilin in neuroblastoma N1E-115 cells, as well as in neurons (Schill et al, 2020).…”
Section: Interaction Between the 5-ht 4 R And L1 Modulates Cofilin-1 Phosphorylationmentioning
confidence: 71%
“…The 5-HT 4 R is a seven transmembrane domain receptor that exerts its effects through coupling to the heterotrimeric G s protein, which activates adenylyl cyclase, inducing an increase in cAMP levels and subsequent increase in phosphorylation of downstream effectors mediated by ERK (ERK1 and ERK2, also known as MAPK3 and MAPK1) (Bockaert et al, 1990;Heine et al, 2002;Norum et al, 2003). We have also shown that the 5-HT 4 R is coupled to G 13 proteins to activate the small GTPase RhoA, leading to changes in cellular morphology and spine maturation via modulation of cofilin phosphorylation and actin polymerization (Ponimaskin et al, 2002;Schill et al, 2020). Several studies have suggested that the functions of the 5-HT 4 R may be regulated through receptor homooligomerization (Pellissier et al, 2011), or through heterooligomerization with other G-protein-coupled receptors (GPCRs) (Berthouze et al, 2005).…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…Experiments were carried out as described previously with minor modifications (Bijata et al, 2015;Schill et al, 2020). Briefly, for biochemical determination of RhoA/Cdc42 activity TA muscles were homogenized in lysis buffer [25 mM HEPES (pH 7.5), 150 mM NaCl, 1% Nonidet P-40, 10 mM MgCl2, 1 mM ethylenediaminetetraacetic acid (EDTA), and 2% glycerol] and centrifuged at 14000 × g for 10 min at 4 • C. The extracts were incubated with GST-PAK-PBD fusion protein that had been conjugated with glutathione beads (for Cdc42; Cell BioLabs) at 4 • C overnight or an anti-active RhoA monoclonal antibody and protein A/G Agarose beads (for RhoA, Neweast Biosciences) for 1 h at 4 • C and then washed three times with lysis buffer.…”
Section: Rhoa/cdc42 Activity Assaymentioning
confidence: 99%